Using fuzzy logic to control dynamic loads on road-building machine construction elements - Koval, O. A.; Minka, S. V.; Коваль, О. А.; Мінка, С. В.; Коваль, А. А.; Минка, С. В. (Харківський національний автомобільно-дорожній університет, 2020)
The results of researches concerning the application of fuzzy set theory for the classification of results of control of dynamic loads on the elements of construction of road-building machines are presented.
Використання нечіткої логіки для контролю динамічних навантажень на елементи конструкції дорожньої машини
Применение нечеткой логики для контроля динамических нагрузок на элементы конструкции дорожной машины
Keywords: road-making machine; fuzzy logic; classification; membership function; term-set; fuzzy set; diagnostics; дорожня машина; нечітка логіка; класифікація; функція належності; терм-множина; нечітка множина; діагностика; дорожная машина; нечеткая логика; классификация; функция принадлежности; терм-множество; нечеткое множество; диагностика; 658.012; 10.30977/BUL.2219-5548.2020.88.1.107